Comparison between immunofixation and electrophoresis for the early detection of relapsed multiple myeloma - Marta Helena C. Aita; Luiz Claudio Arantes; Bruno C. Aita; José Edson P. Silva (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT Introduction: Multiple myeloma (MM) is an incurable progressive hematological neoplasia characterized by heterogeneous evolution and by relapses after therapy. Objective: Compare the effectiveness of serum immunofixation (SIF) and electrophoresis (SPE) techniques in the detection of relapses in MM patients undergoing treatment at the University Hospital of Santa Maria (HUSM). Material and methods: The study was conducted from January 2012 to July 2014 and included 52 patients from HUSM with confirmed diagnosis of MM. The retrospective monitoring based on laboratory analyses indicated that nine of these patients relapsed, in whom it was possible to compare the effectiveness of SIF and SPE techniques for detecting relapses. Results: For the nine patients, SIF always detected MM relapses earlier than SPE, with a precocity ranging from 2.0 to 18.8 months, for an average of 6.6 months. Discussion and conclusion: The results indicated that SIF was more effective than SPE for the early detection of relapses, regardless of the class and type of M component (mono/biclonal). Therefore, the use of SIF allows for better monitoring of MM patients, especially for the detection of relapses, thereby helping in choosing the most appropriate therapy and resulting in increased duration of survival period free of disease.